Development of skeletal muscle and expression of myogenic regulatory factors during embryonic development in Jinding ducks (Anas platyrhynchos domestica). (28th April 2014) - Zhu, Chunhong; Gi, Gaige; Tao, Zhiyun; Song, Chi; Zhu, Wenqi; Song, Weitao; Li, Huifang
Abstract : The important roles of myogenic regulatory factors (MRF) in mammalian skeletal myogenesis have been well studied, but few equivalent studies have been performed in poultry. The expression pattern of MRF during the embryonic development of skeletal muscle in ducks remains unknown. In this study, we identified Myf5, Myf6, MyoD, and myogenin genes in Jinding ducks ( Anas platyrhynchos domestica ) and quantified their expression levels in breast muscle (BM) and leg muscle (LM) at embryonic d 13, 17, 21, 25, and 27 by real-time reverse-transcription PCR. Body weight and muscle weight show different developmental patterns. The MRF genes were expressed in both BM and LM, but with different expression patterns. The MyoD gene showed lower expression levels in BM before embryonic d 21 compared with LM, whereas the opposite pattern was found later. The higher expression level of MyoD, as well its lagged expression pattern in BM, suggest that the MyoD gene may be involved in maintaining the development of different muscles. Correlation analysis showed that myogenin gene expression levels were significantly negatively correlated with BW and muscle weight in both BM and LM ( P < 0.001), and MyoD and Myf6 gene expression levels were more strongly correlated with muscle weight in LM than in BM. The results of this study provide novel evidence for MRF expression in ducks in embryonic stage- and skeletal muscle-dependent manners, and provide a foundation for understanding the molecular control of skeletal muscle growth in duck breeds.